Analysis of Work-Life Balance and Resilience: For Support Employee Performance in Logistics Company - Primadi Candra Susanto; Josua Panatap Soehaditama; Wenny Desty Febrian; Bekti Setiadi; Rachmat Pramukty (International Journal of Integrative Sciences, 2023)
The aim of this scholarly paper is to establish and strengthen the current research outcomes pertaining to the variables examined in this scientific manuscript. The research methodology used is qualitative, using a mini-review of journal articles related to variables, and this will be completed later in this study.  A metric table will be displayed to display scientific articles from various journals in Table 1 and Table 2.  The results of research in this scientific article from the objectives of existing research then the findings by researchers related to the use of variables in this scientific article are proven, true, and strong with the results of research, and also there are several studies from the findings of researchers also related to objects, namely logistics, so in this scientific article the proof is true, strong, and can be used as a basis for further research. There are several variables that are found as gaps to be used in future research by other researchers in the description of scientific articles found and described in this scientific article